Performance indicators in multiobjective optimization - Audet, Charles; Bigeon, Jean; Cartier, Dominique; Le Digabel, Sébastien; Salomon, Ludovic (European journal of operational research, 2021)
•Summarizes elements of Pareto front approximations developed over the last 20 years.•63 performance indicators to measure the quality of Pareto front approximations.•Indicators are partitioned into 4 groups according to their properties.•Strengths and weaknesses of the performance indicators are systematically analyzed.•Many applications of performance indicators are presented. In recent years, the development of new algorithms for multiobjective optimization has considerably grown. A large number of performance indicators has been introduced to measure the quality of Pareto front approximations produced by these algorithms. In this work, we propose a review of a total of 63 performance indicators partitioned into four groups according to their properties: cardinality, convergence, distribution and spread. Applications of these indicators are presented as well.